2016
DOI: 10.1021/acs.jpcc.6b08630
|View full text |Cite
|
Sign up to set email alerts
|

Localized Surface Plasmon Resonance Assisted Photothermal Catalysis of CO and Toluene Oxidation over Pd–CeO2 Catalyst under Visible Light Irradiation

Abstract: The extinction peak of Pd particles generally locates at the ultraviolet light region, suggesting that only 4% of solar light can be absorbed. Furthermore, the efficiency of LSPR hot electrons converted to chemical energy of reaction is very low due to the fast relaxation of carriers. It is extremely valuable to design Pd-based catalysts which have strong response to the visible light irradiation and high efficiency in photon to chemical energy. The Pd–CeO2 catalyst was synthesized via the hexadecyl­trimethyl­… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 48 publications
2
35
1
Order By: Relevance
“…At the same time, analysis of the literature data showed that some previously described similar compounds had a markedly lower catalytic activity ( Table 1). The materials described in [1][2][3][4] allowed complete oxidization of carbon monoxide only at temperatures over 100 • C. However, materials with low-temperature catalytic activity are also mentioned (e.g., the data mentioned in [5,6,8] for ceria supported Pd NPs are close to those obtained in this study). Such a difference in the temperatures of complete conversions can be associated with the location of metal NPs on various surfaces of CeO 2 -(100) or (111).…”
Section: Catalytic Activitysupporting
confidence: 80%
See 1 more Smart Citation
“…At the same time, analysis of the literature data showed that some previously described similar compounds had a markedly lower catalytic activity ( Table 1). The materials described in [1][2][3][4] allowed complete oxidization of carbon monoxide only at temperatures over 100 • C. However, materials with low-temperature catalytic activity are also mentioned (e.g., the data mentioned in [5,6,8] for ceria supported Pd NPs are close to those obtained in this study). Such a difference in the temperatures of complete conversions can be associated with the location of metal NPs on various surfaces of CeO 2 -(100) or (111).…”
Section: Catalytic Activitysupporting
confidence: 80%
“…Supported noble-metal nanoclusters are well-known catalysts for diverse hydrogenation and oxidation reactions, particularly in CO oxidation. A number of attempts [1][2][3][4][5][6][7][8] were made to synthesize a catalyst on the basis of supported NPs with a high activity at low temperatures. The catalytic activity of NPs depends on the size and shape of the NPs [9], the material of the support [10] and the functionalization [11] and composition [12].…”
Section: Introductionmentioning
confidence: 99%
“…According to the Ce 3d spectra (Figure 5a), the spectra for all catalysts were fitted into eight contributions and the features assigned to the spin‐orbit components of Ce 3d 3/2 and Ce 3d 5/2. [ 50–53 ] As can be seen from Figure 5a, the characteristic peaks of the Ce 4+ 3d 5/2 species are labelled V, V″ and V‴, and the Ce 4+ 3d 3/2 species are labelled U, U″ and U‴. [ 54,55 ] The couple peaks V′ and U′ are assigned to Ce 3+ 3d 5/2 and Ce 3+ 3d 3/2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[136] Interested readers are suggested to read several recent reviews on this topic. [137] We list this category here because many of these plasmonic materials are also known co-catalysts, such as metals including Au, [138] Ag, [139] Pd, [140] Cu, [141] Al, [142] and non-metals including Cu 2−x Se, [143] Cu 2−x S, [144] WO 3−x [145] and each of them features unique resonant photon wavelengths. Importantly, the resonant photon wavelength of the plasmonic nanoparticles can be tuned by varying their sizes, shapes, and material compositions.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%